(untitled) (Communications in Computational Physics, 2007)
We propose a theoretical model of the double ionization of homonuclear diatomic targets by fast electron impact. By application of two-effective-center continuum waves to describe the ejected electrons in the exit channel and by use of Nordsieck-type integrals, an expression has been obtained by an analytical treatment for the fivefold differential cross section, the relevant quantity to describe the kinematically complete collisions in the coplanar geometry. The correlate motion of the ejected electrons is taken into account by means of adequate Sommerfeld parameters.